HERPES INFECTION DURING PREGNANCY - Niyozova Durdonа (Scholars Digest Publishing, 2023)
Herpes simplex virus remains one of the most common etiological factors of infectious and inflammatory diseases of the reproductive system in women. This review presents the main morphological properties of the virus, pathogenesis and clinical manifestations of herpetic infection, current data on the incidence in Russia and other countries among the entire population and pregnant women, identified risk groups for the development of herpetic infection (depending on gender, age, number of sexual partners, etc.). The most frequent complications of pregnancy and childbirth in this group of patients (severe forms of gestosis, antiphospholipid syndrome, thrombophilia, premature rupture of fetal membranes, spontaneous termination of pregnancy, etc.) are described, as well as data on intrauterine fetal malformations (ventriculomegaly, corpus callosum dysgenesis, porencephaly, microcephaly, hydrocephalus and microphthalmia, etc.) possible ways of transmission of infection from mother to child during gestation and after childbirth are analyzed. The currently accepted approaches to the diagnosis and treatment of pregnant women with herpes virus infection, as well as indications for natural delivery or caesarean section, are described.
Keywords: herpes virus, spontaneous abortion, intrauterine malformations, genital herpes, pregnancy.